MODEL AIR (AUDITORY, INTELLECTUALLY, REPETITION) DENGAN STRATEGI PENINJAUAN KEMBALI UNTUK MENINGKATKAN KREATIVITAS DAN KEAKTIFAN SISWA DI SMA YASMIDA KEC. AMBARAWA KAB. PRINGSEWU - Muhtarom, Muhtarom; Mustofa, Dwi Rohmadi; Idris, Muhammad (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2018)
AbstractThis study aims to improve creativity and student learning outcomes on learning Sociology class X SMA Yasmida Ambarawa. In general, this research seeks to improve the creativity and learning outcomes of students by using AIR learning model with Review Strategy.This type of research is Classroom Action Research (PTK). The subjects of this study are the students of grade X SMA Yasmida Ambarawa which amounted to 26 people. The object of this research is the implementation of Sociology learning by using AIR learning model with Review Strategy. Classroom Action Research is done in 2 cycles, each cycle consists of 2 meetings.The results showed that there is an increase of creativity and Activity of students by applying AIR model learning with Review Strategy. Student creativity is seen from all indicator of creativity and Student Activity is improving. In the first cycle of creativity of 60.66%, in the second cycle of 79.96%, while the student's activity also increased from 70% to 85%. Creativity can be seen from the ability to generate many ideas, the ability to propose a variety of solutions to problems, the ability to find answers, tend to give more answers, respond to questions posed, have many questions, and be able to describe things in detail. Student activity is seen from observing, asking, trying, reasoning, tasting, and creating. Students can listen, think, share in groups, and review the material with pleasure so as to provide opportunities for students to hone their own ability, responsibility, and self-belief.